2007
DOI: 10.1093/jhered/esm064
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity in a Feral Horse Population from Sable Island, Canada

Abstract: The present-day Sable Island horse population, inhabiting an island off the eastern coast of Canada, is believed to have originated mainly from horses confiscated from the early French settlers in Nova Scotia in the latter half of the 18th century. In 1960, the Sable Island horses were given legal protected status and no human interference has since been allowed. The objective of this study was to characterize the current genetic diversity in Sable Island horses in comparison to 15 other horse breeds commonly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 33 publications
7
54
1
3
Order By: Relevance
“…The H o was highest at 0.770 in the Kerry Bog and lowest in the Exmoor at 0.569. These results are consistent with other published studies, in which fewer loci or a smaller sample size were used, for several populations including the Connemara, Fjord, Haflinger, Newfoundland, Standardbred and Sable Island (Luís et al, 2007;Plante et al, 2007;Leroy et al, 2009). In contrast, others have also found slightly higher values in the Connemara, Exmoor, Fell, Icelandic, Shetland, New Forest and Caspian (Cothran, 2004;Luís et al, 2007;Leroy et al, 2009).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…The H o was highest at 0.770 in the Kerry Bog and lowest in the Exmoor at 0.569. These results are consistent with other published studies, in which fewer loci or a smaller sample size were used, for several populations including the Connemara, Fjord, Haflinger, Newfoundland, Standardbred and Sable Island (Luís et al, 2007;Plante et al, 2007;Leroy et al, 2009). In contrast, others have also found slightly higher values in the Connemara, Exmoor, Fell, Icelandic, Shetland, New Forest and Caspian (Cothran, 2004;Luís et al, 2007;Leroy et al, 2009).…”
Section: Resultssupporting
confidence: 91%
“…These values are similar to previously reported data in which 10% to 17% and 83% to 90% of genetic diversity could be explained by breed differences and differences within individuals, respectively (Aberle et al, 2004;Glowatzki-Mullis et al, 2006;Plante et al, 2007). Individual assignment tests based on the maximum likelihood methods to predefined populations found that 98% of individuals were correctly assigned to their respective group (Tables 2 and 3).…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations